Evaluation of the anti-inflammatory effect of Yograj Guggul: an in vitro study - Supriya Bhalerao,; Renuka Munshi,; Samidha Joshi, (International Journal of Phytomedicine, 2017)
Yograj Guggul (YG) is a poly-herbal formulation extensively used by Ayurvedic practitioners to treat inflammatory conditions. However there are no reports evaluating its effect on the various enzymes involved in the inflammatory pathway. Hence the present was carried out to evaluate the anti-inflammatory effect of YG, on inhibition of Cyclooxygenase (COX) - 1 & 2 and 5-Lipoxygenase (LOX) enzymes in vitro. Three concentrations (25, 50 and 100µg/ml) of the aqueous extract of YG were studied on the inhibition of COX 1 & 2 and 5-LOX enzymes by Enzyme Immuno Assay (EIA). Aspirin was used as a positive control at concentration corresponding to its anti-inflammatory human dose (100µg/ml).YG exhibited maximum inhibition of both COX-1 &COX-2 enzymes at 100µg/ml that was comparable to aspirin. Interestingly, YG showed a dose dependent increase in percentage inhibition of 5-LOX enzyme with maximum effect at 100µg/ml which was significantly higher than that exhibited by aspirin. YG inhibits both COX enzymes indicating its potential as an anti-inflammatory agent. The 5-LOX inhibitory activity exhibited by YG provides a lead to explore its role further as a dual inhibitor of COX/5-LOX pathways and also to investigate its role to treat inflammatory respiratory disorders.